Better Small Talk Talk to Anyone, Avoid Awkwardness, Generate Deep Conversations, and Make Real Friends - Patrick King (Great Britain Independently published, 2020)
Networking events suck, but they can suck less. What to say and when to say to be likable, connect, and make a memorable impression.
Keywords: Cpmmunication